The Impact of Morfofonemics: Unveiling the Secrets of Word Structure Formation in Indonesian - Maulana, Adam; Zahra , Naila Az; Natania, Mega Lefina; Sofyeni , Rezzy Apriska; Mutiara , Rizki Indah; Pebriana , Putri Hana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to examine the influence of morphophonemic processes on word structure in Indonesian. Morphophonemics is the study of sound changes that occur as a result of morphological processes, such as affixation, reduplication and compounding. In Indonesian, these sound changes often affect the basic form of words, resulting in phonological variations that have certain grammatical meanings. The method used in this research is descriptive qualitative by analyzing data in the form of words in Indonesian which experience changes in form due to morphophonemic processes. The research results show that sound changes, such as leaching, insertion, and changes in vowels or consonants, play an important role in forming word structures that comply with the rules of Indonesian morphology and phonology. These findings contribute to a deeper understanding of the relationship between morphology and phonology in word formation, as well as its implications for Indonesian language learning, especially in aspects of grammar and linguistic teaching.